Use and Perceptions of the Availability of Local Government and Nonprofit Services in Diverse Urban Settings. (October 2019) - AbouAssi, Khaldoun; Faulk, Lewis; Tran, Long; Shaffer, Lilli; Kim, Minjung
This analysis tests fundamental nonprofit theory using individual-level demand-side data, which complements existing studies that have relied on organizational- and community-level variables alone. We use survey and administrative data to test the relationship between individuals' perceptions and use of local government services and their reported use of nonprofit services, controlling for the density of organizations around respondents' addresses. Individuals who report being better served by government services are significantly more likely to report using nonprofit services—while individuals who report being unserved by government are also less likely to report access to nonprofits, despite the actual density of organizations around them. These findings support theories of interdependence between government and nonprofit sectors. However, income-based disparities in perceived access to nonprofit services highlight persistent gaps in serving all individuals on the local level.